ANALYSIS OF THE ROLE OF THE MANINDO SIABU COOPERATIVE PARTNERS IN INCREASING THE INCOME OF COOPERATIVE MEMBERS (CASE STUDY IN SIMANINGGIR VILLAGE) - anni sofiyah; kamaluddin ritonga; ihdi aini; ali hardana (Journal Of Sharia Banking, 2020)
Mitra Manindo Siabu Cooperative is the target place for the community's economic movement, where cooperation in it colors the Islamic values of the community's economic life. Community income is the development of Mitra Manindo Cooperative. The beginning of the establishment of the Mitra Mnaindo Cooperative was due to the desire to increase the income of each cooperative member who was actively involved in the operation of the cooperative, but in the last 5 years the members of the Mitra Manindo Cooperative have decreased, even though one of the factors that affect the income of members is the participation of the members of the cooperative itself. . The theory in this study is related to income theory, discussing the meaning of income and income functions. Cooperative theory discusses the meaning of cooperatives, cooperative management, cooperative legal basis, types of cooperatives, sharia cooperative principles, sources of cooperative funds, cooperative income. Role theory discusses the role of cooperatives in Indonesia, the role of sharia cooperatives, and the role of cooperatives in increasing income. This type of research is a qualitative research with descriptive methods that describe how what actually happened in the field with data collection techniques are interviews, observation and documentation directly in Simaninggir Village. The data used in this study are primary and secondary data. The data analysis carried out in this qualitative descriptive study was conducted by direct interviews by giving 8 questions to the informants totaling 20 people. Techniques for checking the validity of the data are: triangulation, using reference materials, and extending observations. The results of this study are the Mitra Manindo Cooperative has fulfilled its role as a financial institution, and has helped the Simaninggir Village community increase the income of members, especially members of the Mitra Manindo Cooperative by providing business capital assistance to cooperative members, and reducing the dependence of members on existing cooperatives in order to improve economic welfare. its members.